Comparative Analysis of Roadway Reinforcement Effects Based on Fluid-Solid Coupling in the Fractured Zone of Water-Rich Fault. (6th September 2018) - Zhang, Jihua; Dong, Yun; Chen, Yadong; Jiang, Yang; Sun, Huasheng; Fan, Yuqing; Wang, Chun
Abstract : Water inrush is a common geological disaster during the roadway excavation process in the broken zone of water-rich faults. In this paper, the 15107 mining roadway built by Yuxing coal mine in such a fault zone was used as a case study to determine the water content of the surrounding rocks and a fault zone using the transient electromagnetic method (TEM). Also, the mechanics characteristics of such rocks in both saturated and unsaturated states were analyzed, a computational model for fluid-solid coupling in the water-rich fault fracture zone was established, and the permeability coefficient of the rocks under both shield support and bolt-grouting support was compared, along with analyzing the changes in pore pressure, fissure water velocity, and characteristics of deformation in the surrounding rocks. The numerical simulation results show that the fault range has an influence of about 20 m, which causes the forms of permeability coefficient to change like a hump. The permeability coefficient in the fractured zone is the largest, and the mutation rate at the fault plane is faster. Bolting not only reduces the permeability coefficient of the surrounding rock that is 1/10 of the beam support but also prevents the roof fissure water inrushing the roadway and the surrounding rock of the floor, while also causing the pore-water pressure to decrease, even reduce to zero, in front of the working face and floor. The flow velocity of the fissure water can be decreased by bolting, which can effectively control the deformation of the surrounding rock by 38.7%∼65% compared with the shield support. The practice results show that this method can effectively recover the cracks surrounding the mining roadway and stop gushing water. Concurrently, it successfully controls deformation of the surrounding rocks in the fault zone, thus ensuring stability of the roadway and facilitating safer mining production.